The excessive use of force majeure for the extension of Deadlines in electric sector projects - Aguirre Ramírez, Mayra (2019)
During the last decade, the failure to meet public works execution deadlines has been a frequent matter. Particularly among the electricity sector, private companies have loosened established project execution deadlines by resorting to force majeure as a justification for obtaining an extended deadline. However, have these granted extensions really been justified in events of force majeure?.In this article, the author explains the regimes under which electric concessions are granted to further detail the regulation established electric project deadlines and the consequences of its non-compliance. Subsequently, the author reviews the regulation and doctrine on force majeure and lastly, acutely analyzes its use as justification in the deadline extensions granted in recent years.